Laboratory methods supporting measles surveillance in Queensland, Australia, 2010–2017 - McMahon, Jamie L. (Access Microbiol, 2020)
PURPOSE. Australia was officially recognised as having eliminated endemic measles transmission in 2014. Maintaining laboratory support for surveillance of vaccine-preventable diseases, such as measles, is an essential component of reaching and maintaining transmission-free status. METHODOLOGY. Real-time and conventional PCR-based tools were used to detect, differentiate from measles vaccine virus (MeVV), and sequence fragments of measles viruses (MeV) identified from specimens collected in Queensland. Specimens were mostly from travellers who had visited or returned to Queensland from international or interstate sites or been in contact with a case from either group. RESULTS. Between 2010 and 2017, 13 678 specimens were tested in our laboratory using real-time RT-PCR (RT-rPCR), identifying 533 positives. Most specimens were swabs (70.98 %) and urines (25.56 %). A MeVV RT-rPCR was used on request and identified 154 instances of MeVV. MeV-positive extracts were genotyped as required. Genotypes identified among sequenced specimens included B3, D4, D8, D9, G3, and H1 as well as members of clade A as expected from the detection of MeV among virus introductions due to global travel and vaccination. CONCLUSION. We describe the workflow employed and results from our laboratory between 2010 and 2017 for the sensitive detection of MeV infection, supporting high-quality surveillance to ensure the maintenance of Australia’s measles-free status.